The yawn book - Kim, Diana (Clarion books, an imprint of HarperCollinsPublishers, 2022)
"Why do we yawn? Do animals yawn? And why are yawns so CONTAGIOUS? Learn the answers to these questions and more in this fact-filled and funny nonfiction picture book. Why did you yawn before your piano recital? Do you yawn more than your grandmother? And is your pet dog really yawning because you are? Find out in The Yawn Book, a funny and fascinating book of facts, including the most unbelievable one: no one knows for sure why we yawn at all." --